Peningkatan Pengetahuan Kesiapsiagaan Bencana melalui Edukasi bagi Siswa Sekolah Dasar Negeri 98/IV Kota Jambi: Improving Disaster Preparedness Knowledge through Education for Students of State Elementary School 98/IV, Jambi City - Yosi Oktarina; Nurhusna Nurhusna; Kamariyah Kamariyah; Sri Mulyani; Yusnilawati Yusnilawati; Luri Mekeama; Yulia Indah Permata Sari; Putri Irwanti Sari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Flooding is a frequent disaster in Indonesia. Children, as a vulnerable group, require adequate preparedness to protect themselves when disasters strike. This activity aimed to increase elementary school students' knowledge of flood disaster preparedness. The activity was carried out at SDN 98/IV Kota Jambi involving 40 sixth-grade students. Methods used included interactive lectures, discussions, demonstrations, and simulations delivered via presentation media. The material provided covered an introduction to floods, preparedness measures before, during, and after floods, prevention of post-flood diseases, healthy living behaviors, handwashing practices, and waste sorting. The evaluation was conducted using a disaster preparedness knowledge questionnaire with 15 questions. The results showed an increase in students' knowledge after the educational intervention, as indicated by a rise in the proportion in the "very good" knowledge category from 70% to 87.5%. This indicates that disaster preparedness education is effective in improving students' understanding and readiness to face flood risks. It is hoped that this activity can be implemented continuously and integrated into school learning to strengthen a culture of disaster awareness from an early age.